2011
DOI: 10.1021/ja208581r
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Diffusion in Thin Polymer Films As Observed by High-Temperature Single-Molecule Fluorescence Microscopy

Abstract: Single-molecule fluorescence microscopy was used to investigate the dynamics of perylene diimide (PDI) molecules in thin supported polystyrene (PS) films at temperatures up to 135 °C. Such high temperatures, so far unreached in single-molecule spectroscopy studies, were achieved using a custom-built setup which allows for restricting the heated mass to a minimum. This enables temperature-dependent single-molecule fluorescence studies of structural dynamics in the temperature range most relevant to the processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 59 publications
9
107
2
1
Order By: Relevance
“…42 By using the single-molecule uorescence microscopy, Wöll's group found that the temperature dependence of fraction of mobile molecules in polystyrene lms exhibited similar trends with that of PSM. 42 By using the single-molecule uorescence microscopy, Wöll's group found that the temperature dependence of fraction of mobile molecules in polystyrene lms exhibited similar trends with that of PSM.…”
Section: Resultsmentioning
confidence: 97%
“…42 By using the single-molecule uorescence microscopy, Wöll's group found that the temperature dependence of fraction of mobile molecules in polystyrene lms exhibited similar trends with that of PSM. 42 By using the single-molecule uorescence microscopy, Wöll's group found that the temperature dependence of fraction of mobile molecules in polystyrene lms exhibited similar trends with that of PSM.…”
Section: Resultsmentioning
confidence: 97%
“…For temperature-dependent lifetime measurements, an indium tin oxide (ITO) coverslip was used instead. The temperature of the ITO coverslip was then resistively heated to temperatures of up to 160°C ( 40 ). FLIM measurements in live cells were done on the microscope with the Petri dishes either being held at room temperature or at 37°C using a commercial heating stage (Tokai Hit, Japan).…”
Section: Flim Measurementsmentioning
confidence: 99%
“…Singlemolecule imaging studies have been revealing the spatiotemporal heterogeneity of polymer dynamics by visualizing the motion of individual polymer chains [32][33][34][35][36] or small fluorophores embedded in polymer matrices. [37][38][39][40][41][42][43][44] Using single-molecule localization and tracking (SMLT) technique, we previously reported the multimode diffusion of a cyclic and dicyclic polymers under the entangled conditions by incorporating a fluorophore into the chains. 17,45,46 These studies have suggested a direct connection between the conformational state of the chains and the diffusive motion.…”
Section: Introductionmentioning
confidence: 99%